Cathepsin B inhibitors: Further exploration of the nitroxoline core. Issue 7 (15th April 2018) - Sosič, Izidor; Mitrović, Ana; Ćurić, Hrvoje; Knez, Damijan; Brodnik Žugelj, Helena; Štefane, Bogdan; Kos, Janko; Gobec, Stanislav
Graphical abstract: Highlights: A focused library of more than 60 nitroxoline derivatives was synthesized. The ability of nitroxoline derivatives to inhibit endopeptidase and exopeptidase activities of cathepsin B was determined. Several derivatives showed promising efficacy in tumor-cell-based assays. The structural requirements for cathepsin B inhibition were further defined. Abstract: Human cathepsin B is a cysteine protease with many house-keeping functions, such as intracellular proteolysis within lysosomes. Its increased activity and expression have been strongly associated with many pathological processes, including cancers. We present here the design and synthesis of novel derivatives of nitroxoline as inhibitors of cathepsin B. These were prepared either by omitting the pyridine part, or by modifying positions 2, 7, and 8 of nitroxoline. All compounds were evaluated for their ability to inhibit endopeptidase and exopeptidase activities of cathepsin B. For the most promising inhibitors, the ability to reduce extracellular and intracellular collagen IV degradation was determined, followed by their evaluation in cell-based in vitro models of tumor invasion. The presented data show that we have further defined the structural requirements for cathepsin B inhibition by nitroxoline derivatives and provided additional knowledge that could lead to non-peptidic compounds with usefulness against tumor progression.